Formulasi Krim Minyak Biji Bunga Matahari (Helianthus annuus L.) dengan Variasi Konsentrasi Setil Alkohol sebagai Anti Jerawat - Lusiana Ariani; Nur Miftahurrohmah; Kartiningsih Kartiningsih; Meilisa Ang (Fakultas Farmasi Universitas Pancasila, 2020)
Acne is an inflammatory condition that was caused by Propionibacterium acnes. Sunfl owerseeds (Helianthus annuus L.) with terpenoids and linoleic acid could prevent and treat acne. In theprevious study, sunfl ower seed oil had a Minimum Inhibitory Concentration (MIC) value for P. acnesbacteria ≥1.5% with a Diameter Inhibitory Zone 15.27 mm which was classifi ed as a strong antibacterialagent. This study was intended to develope cream formula (F1-F4) using variations of cetyl alcoholconcentrations of 8, 10, 12% and blanko respectively. The creams were formulated by heating the waterphase and the oil phase separately at 70˚C, then stirred to form the cream. The prepared formulations wereevaluated for organoleptic, homogeneity, type of cream, viscosity and rheology, spread ability, globulesize, centrifugation, and pH. The organoleptic results showed that the cream was white, odorless, softin texture and homogeneous with the type of oil in water (O/W) cream. The viscosity test showed thatthe viscosity of F1-F3 formulas were 490.29; 3886.29; 22510.67 cP and F4 of 111.04 cP with plasticthixotropic fl ow properties. Formula F1-F4 had a spread ability of 8.9; 5,4; 4,4; 7.3 cm2, the globulesizes were 137.78; 133,33; 151.11; 94.44 μm, did not show phase separation during centrifugation andthe pH of the F1-F3 formula were 6.3 and F4 was 5.93. It may be concluded that the evaluation of thephysical and chemical quality of sunfl ower seed oil cream are within the acceptable standard.